Fatty acid composition and docosahexaenoic acid (DHA) content of the heterotrophic dinoflagellate Oxyrrhis marina fed on dried yeast: compared with algal prey - Yoon, Eun Young; Park, Jaeyeon; Jeong, Hae Jin; Rho, Jung-Rae (Algae (Korean Phycological Society), 2017)
The heterotrophic dinoflagellate Oxyrrhis marina is known to produce high levels of docosahexaenoic acid (DHA) when fed on diverse algal prey. However, large-scale culturing of algal prey species is not easy and requires a large amount of budget, and thus more easily cultivable and low-cost prey is required. Dried yeast was selected as a strong candidate for an alternative prey in our preliminary tests. Thus, we explored the fatty acid composition and DHA production of O. marina fed on dried yeast and compared these results to those of O. marina fed on two algal prey species: the phototrophic dinoflagellate Amphidinium carterae and chlorophyte Chlorella sp. powder. O. marina fed on dried yeast, which does not contain DHA, produced the same high level of DHA as those fed on DHA-containing A. carterae. This indicates that O. marina is likely to produce DHA by itself regardless of prey items. Furthermore, the DHA content (and portion of total fatty acid methyl esters) of O. marina satiated with dried yeast, 52.40 pg per cell (and 25.9%), was considerably greater than that of O. marina fed on A. carterae (26.91 pg per cell; 15.7%) or powder of Chlorella sp. powder (21.24 pg per cell; 16.7%). The cost of dried yeast (approximately 10 US dollars for 1 kg dried yeast) was much lower than that of obtaining the algal prey (approximately 160 US dollars for 1 kg A. carterae). Therefore, compared to conventional algal prey, dried yeast is a more easily obtainable and lower-cost prey for use in the production of DHA by O. marina.